MEANINGFUL HUMAN-MACHINE INTERACTION: SOME SUGGESTIONS FROM THE PERSPECTIVE OF AUGMENTED INTELLIGENCE - Martina PROPERZI (Studia Universitatis Babeș-Bolyai. Philosophia, 2022)
In this article I will address the issue of the meaning of human-machine interaction as it is configured today in the light of substantial results achieved in the design and the manufacture of Artificial Intelligence (AI) systems. My starting point is a refined solution for meaningful AI recently suggested by Froese and Taguchi from the perspective of so-called augmented intelligence. Interpreted as a kind of human-machine interaction, augmented intelligence distinguishes itself by the fact that it merges the interacting poles into a new hybrid entity. After having clarified the technical and the methodological background of my proposal, I will discuss a case of study of so-called bio-synthetic augmentation, where hybridisation overlaps with the cyborgisation of the human body.